Cytotoxic and antioxidant activity of the biogenic bismuth nanoparticles produced by Delftia sp. SFG. (August 2018) - Shakibaie, Mojtaba; Amiri-Moghadam, Parinaz; Ghazanfari, Mehran; Adeli-Sardou, Mahboubeh; Jafari, Mandana; Forootanfar, Hamid
Graphical abstract: a) Screening of salty soil samples for isolation of Bi NPs producing bacterial strain on b) Bi 3+ ions supplemented Muller–Hinton agar plate and c) nutrient broth medium including Bi 3+ ions. d) purification of the produced Bi NPs using three phase partitioning system and their characterization using transmission electron microscopy (TEM) and equipped scanning electron microscope (SEM) methods. Highlights: A bismuth nanoparticle (Bi NPs) producer bacterium, Delftia sp. SFG, was screened. The Bi NPs was purified by a three phase partitioning system and characterized. Cytotoxicity and antioxidant activity of biogenic Bi NPs were determined. Abstract: In the present investigation a bismuth nanoparticles (Bi NPs) producing bacterial strain (designated as Delftia sp. SFG) was isolated from salt marsh and the biogenic Bi NPs was purified, characterized, and their cytotoxic and antioxidant activities were determined. The spherical shaped Bi NPs was inspected by transmission electron microscopy (TEM), scanning electron microscopy (SEM) equipped with energy dispersive X-ray (EDX) microanalyzer, and X-ray diffraction spectroscopy (XRD) method. Furthermore, the related size distribution pattern (20–120 nm), UV–vis and Fourier transform infrared (FTIR) spectrums of the produced Bi NPs were determined. The attained results of cytotoxic effect (determined by MTT-based colorimetric assay) of the purified Bi NPs revealed IC50 of 10.9 ± 0.9 μg mL −1, 35.4 ± 0.5 μg mL −1, and 42.8 ± 1.7 μg mL −1 against A549, MCF-7, and 3T3 cell lines. Determination of antioxidant activity showed IC50 values of 123.1 μg mL −1 and 307.2 μg mL −1 for butylated hydroxyanisole (BHA) and Bi NPs, respectively.